Implementasi manajemen akreditasi perpustakaan perguruan tinggi berstandar nasional di Universitas Negeri Malang - Teguh Yudi Cahyono; Umi Masruroh; Sarwono Sarwono (Jurnal Kajian Informasi dan Perpustakaan, 2021)
University library accreditation aims to improve library quality. In order to get formal recognition from the state, university libraries apply for accreditation to the National Library to assess whether they have met national standards. This study aimed to determine implementation the management of university library accreditation with national standards at the University of Malang (UM). The research method used the descriptive qualitative method, which described management functions performed by UM library in the university library accreditation. The results research showed that library accreditation management carries out planning, organizing, implementing, and monitoring processes. Management functions are described in accreditation ranging from planning to supervisory functions. The planning process is to design accreditation activities structurally and organizationally to achieve the expected conditions through team planning, physical evidence, and accreditation performance. Organizing processes are forming an organizational structure and detailing the duties of accreditation team members to play an effective role by classifying accreditation instruments, organizing teamwork, and accreditation documents. General and technical guidelines for university library accreditation guide the implementation process to obtain optimal performance from the accreditation team through completing documents, preparing for visitations, correcting forms, and conducting self-assessments. The monitoring process avoids deviations by evaluating the administration, budget, forms, performance, and physical evidence of accreditation. The study concludes that the implementation of accreditation management through planning, organizing, implementing, and monitoring aims that the UM library can achieve accreditation objectives, namely obtaining satisfactory results as well as the legitimacy, reputation, and legality of the library.